Potential use of peptides mimicking CRAC/CARC domains as antivirulence therapies to inhibit RTX toxins activities - Vanesa Herlax (Exploration of Drug Science)
In recent years, research efforts have increased to develop new therapeutics aimed at combating antibiotic-resistant bacterial infections. These efforts focus on inhibiting the virulence factors bacteria secrete to proliferate. This review aims to highlight the advances in these antivirulence therapies, with a particular emphasis on those utilizing peptides to inhibit toxin activity. Specifically, we will review the mechanism of action of a group of toxins known as Repeat in ToXins (RTX) and the progress made regarding the use of peptides to inhibit their action. Notably, we will discuss the use of peptides mimicking either cholesterol recognition/interaction amino acid consensus (CRAC) or CARC motifs, which are similar to CRAC motifs but have the opposite orientation, to reduce their interaction with cholesterol in target cells. We will present results corresponding to the inhibition of three characteristic toxins of this group: HlyA from Escherichia coli, LtxA from Aggregatibacter actinomycetemcomitans, and CyaA from Bordetella pertussis. While these advances are very recent, they are promising for the development of new therapies. The advantage of this type of therapy is that it reduces the selective pressure for the growth of resistant bacteria.